New species of cynipid inquilines of the genus Saphonecrus (Hymenoptera: Cynipidae: Synergini) from the Eastern Palaearctic, with a re-appraisal of known species world-wide - Schwéger, Szabina; Melika, George; Tang, Chang-Ti; Yang, Man-Miao; Stone, Graham N.; Nicholls, James A.; Sinclair, Frazer; Hearn, Jack; Bozsó, Miklós; Pénzes, Zsolt (Zootaxa, 2015)
Fifteen new species of cynipid inquilines, Saphonecrus chinensis Tang & Schwéger, S. gilvus Melika & Schwéger, S. globosus Schwéger & Tang, S. leleyi Melika & Schwéger, S. lithocarpii Schwéger & Melika, S. longinuxi Schwéger & Melika, S. morii Schwéger & Tang, S. nantoui Tang, Schwéger & Melika, S. nichollsi Schwéger & Melika, S. pachylomai Schwéger, Tang & Melika, S. robustus Schwéger & Melika, S. saliciniai Melika, Tang & Schwéger, S. shanzhukui Melika & Tang, S. symbioticus Melika & Schwéger, and S. taitungi Schwéger, Tang & Melika, from the Eastern Palaearctic are described. Descriptions, diagnoses, biology, and host associations for the new species, and a key to Palaearctic Saphonecrus species are given. All new taxa form distinct units as demonstrated by the molecular phylogenetic analyses of Palaearctic Saphonecrus species. The status of some earlier described Saphonecrus species is discussed also. The Synergini genus Lithonecrus Nieves-Aldrey & Butterill, 2014 is synonymized with Lithosaphonecrus Tang, Melika & Bozsó, 2013. Three Saphonecrus species are transferred to Synergus: Synergus brevis (Weld) comb. nova, Synergus hupingshanensis (Liu, Yang & Zhu) comb. nova, and Synergus yukawai (Wachi, Ide & Abe) comb. nova. Synophrus vietnamensis Abe, Ide, Konishi & Ueno is transferred to Lithosaphonecrus: Lithosaphonecrus vietnamensis Abe, Ide, Konishi & Ueno), comb. nova. The current number of valid Saphonecrus species worldwide is 36.